Оптимізація часу доїзду автомобілів екстрених служб до місця пожежі - Паснак, Іван; Ренкас, Артур (ТзОВ «Галицька видавнича спілка», 2021)
The article is devoted to the issue of the negative impact of delays in the movement of special rescue vehicles on the effectiveness of their mission. The example of a fire-rescue vehicle shows the dependence of the area of fire on the delay of the arrival of firefighters. The cascading graph of variants of routes of movement of special vehicles to the place of an emergency call is given. The algorithm of choice of the optimal route of motion of special vehicles with given projected delays is given.
Optimization of the duration of emergency vehicle movement to the place of fire
Keywords: 656.13